Ketosis of cattle: causes, consequences and prevention measures - S. V. Huralska; V. M. Olishevskyi (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Bovine ketosis is one of the most common metabolic diseases that significantly affects the productivity of the dairy herd and the economic efficiency of livestock farms. The article discusses the main causes of ketosis, including negative energy balance, dietary disorders, protein and vitamin deficiencies, and excessive mobilization of body fat reserves. Particular attention is paid to the clinical manifestations of the disease, which range from subclinical forms with decreased productivity to severe clinical manifestations such as weight loss, nervous disorders, and intoxication. Based on the analysis of the works of leading scientists in this area, the main methods of diagnosing ketone bodies in blood, milk and urine are presented, as well as recommendations for the timely detection of latent forms of the disease. The main goal of ketosis treatment is to compensate for glucose deficiency in the body, and it should be aimed at restoring energy balance in the first place. Initially, it is necessary to ensure rapid administration of glucose, followed by therapy aimed at maintaining its long-term level. Particular attention is paid to preventive measures, which include optimizing the diet, monitoring the condition of cows in transition, using high-quality feed and regular monitoring of energy balance. The article is based on the results of numerous studies and analyzes the current approach to dairy herd health management. The data presented in the article can be useful for both practicing veterinarians and dairy farm owners.